Interaction of Organophosphorus Pesticides with DNA Nucleotides on a Boron-Doped Diamond Electrode - Garbellini, Gustavo S. [UNESP]; Uliana, Carolina V. [UNESP]; Yamanaka, Hideko [UNESP] (Soc Brasileira Quimica, 2013)
Diamond electrode was used to evaluate the interaction of the nucleotides guanosine monophosphate (GMP) and adenosine monophosphate (AMP) with the pesticides chlorpyrifos, methamidophos and monocrotophos. Changes were observed in the currents and peak potentials of the nucleotide voltammograms in the presence of the pesticides, with dependence on the pesticide concentration (from 5.0 x 10(-7) to 5.0 x 10(-5) mol L-1) and the interaction time (from 1 min to 4 h). This is probably due to binding of the pesticides to the nitrogenous bases present in the nucleotides, which could lead to problems in the DNA replication and biological functions of nucleotides. The pesticides showed stronger interaction with AMP than with GMP. Studies of the interaction of 50 mu g mL(-1) DNA with the pesticides (from 30 min to 4 h and from 1.0 x 10(-6) to 6.0 x 10(-5) mol L-1) did not reveal any peaks relating to double helix opening or DNA unwinding.
Keywords: organophosphorus pesticides; DNA nucleotides; diamond electrode; DNA damage; binding molecules